Influences of cultural capital and internationalization on global competence in higher education: a systematic literature review - Teng, Yiying; Cosier, Meghan E. (Frontiers in Education, 2024)
Introduction: In an increasingly global economy, the Global Competence of students in higher education is a critical area of importance. The purpose of the study was to explore the research on factors that influence an individual’s global competence in both international and Chinese contexts. Methods: Under the umbrella of cultural capital theory and Internationalization, a systematic literature review analyzed and synthesized the empirical studies of global competence from 2013 to 2022. Results: This research revealed that students with higher cultural capital backgrounds obtain more educational opportunities and further exhibit better global competence achievement. Internationalization abroad is a direct and practical pedagogy for global competence acquisition, reflected in student and faculty mobility. Internationalization opportunities in an individual’s home country catalyze global competence. Conclusion: These results highlight that students who have a lower capital background or few opportunities for mobility can reap the potential beneﬁts of global competence attainment through involvement in domestic educational activities.